Selection parameters in six rowed exotic barley (Hordeum vulgare L.) genotypes - Gupta, Pravir Kumar; Pandey, Ashutosh; Kumar, Jitendra; Bahar, Javed (Journal of Cereal Research, 2018)
An experiment involving 70 genotypes of exotic barley was conducted during Rabi 2014-15 at Crop Research Farm, Nawabganj, Kanpur in Randomized Block Design with three replications. Data were recorded for 15 characters. Highly significant positive correlation of grain yield/plant was observed with biological yield/plant, a number of productive tillers/plant, main spike length, while significant positive correlations were observed with a number of grains/spike and shoot length. Doi.org/10.25174/2249-4065/2018/83754